2016
DOI: 10.1149/2.1371607jes
|View full text |Cite
|
Sign up to set email alerts
|

High-Performance Aqueous Organic Flow Battery with Quinone-Based Redox Couples at Both Electrodes

Abstract: We have demonstrated the repeated cycling of a redox flow cell based on water-soluble organic redox couples (ORBAT) at high voltage efficiency, coulombic efficiency and power density. These cells were successfully operated with 4,5-dihydroxybenzene-1,3-disulfonic acid (BQDS) at the positive electrode and anthraquinone-2,6-disulfonic acid (AQDS) at the negative electrode. Reduction of the voltage losses arising from mass transport limitations, and understanding of the chemical transformations of BQDS during cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
265
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 210 publications
(289 citation statements)
references
References 32 publications
20
265
0
1
Order By: Relevance
“…The charge and discharge curves at 100 mA/cm 2 showed a single plateau (Figure 7), which is markedly different from that of the BQDS where multiple plateaus were observed from the very first cycle. 21 Furthermore, with BQDS the first discharge only returned one-third of the first charge capacity, consistent with the transformations caused by the Michael reaction, needing three times the amount of charge to reach the final charged state. When DHDMBS was used, the first charge and discharge capacities were almost equal, proving that there was no Michael transformation occurring with DHDMBS.…”
Section: Resultssupporting
confidence: 62%
See 2 more Smart Citations
“…The charge and discharge curves at 100 mA/cm 2 showed a single plateau (Figure 7), which is markedly different from that of the BQDS where multiple plateaus were observed from the very first cycle. 21 Furthermore, with BQDS the first discharge only returned one-third of the first charge capacity, consistent with the transformations caused by the Michael reaction, needing three times the amount of charge to reach the final charged state. When DHDMBS was used, the first charge and discharge capacities were almost equal, proving that there was no Michael transformation occurring with DHDMBS.…”
Section: Resultssupporting
confidence: 62%
“…13 C NMR chemical shifts were determined relative to the 13 In our previous publication, we demonstrated that changing the starting material from an alkali metal salt to an acid greatly increased its solubility. 21 The acid-form allowed us to reach higher concentration values -as high as 3 M for BQDS and 2 M for AQDS. In turn, this increase in concentration yielded higher operating current densities and improved the overall performance of the cell.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, quinones have been demonstrated as inexpensive electroactive species for aqueous flow batteries [2][3][4][5]. One hundred charge-discharge cycles have been demonstrated in an all-quinone flow battery using a tiron posolyte (positive electrolyte) and an anthraquinone-2,6-disulfonic acid negolyte (negative electrolyte), at 35% depth of discharge, with no mention of capacity retention [5].…”
Section: Introductionmentioning
confidence: 99%
“…One hundred charge-discharge cycles have been demonstrated in an all-quinone flow battery using a tiron posolyte (positive electrolyte) and an anthraquinone-2,6-disulfonic acid negolyte (negative electrolyte), at 35% depth of discharge, with no mention of capacity retention [5]. Our group demonstrated 750 deep cycles of a quinone-bromide flow battery (QBFB) using anthraquinone-2,7-disulfonic acid (AQDS), with 99.84% capacity retention per cycle [6].…”
Section: Introductionmentioning
confidence: 99%